Symptoms of panic disorder may lead to a potential misdiagnosis as a cardiopulmonary disease, particularly in rural areas - Hussain, Mubashir; Shah, Imam Ali (Journal of the Pakistan Medical Association, 2024)
Madam, The hallmark of panic disorder is erratic, recurrent, sudden bouts of severe anxiety referred to as "panic attacks," which render patients fearful of having another episode. These episodes are accompanied by symptoms such as palpitations, shortness of breath, chest tightness, dizziness, choking, fainting, sweating, and neurological symptoms. A study in 2022 suggests that the prevalence of panic attacks is 13.2%, mostly among women, the unemployed, and low-income individuals. The high rate of misdiagnosis (85.6%) is an issue that needs to be addressed.1 Panic symptoms can resemble several serious medical disorders, making a differential diagnosis problematic. However, it could often be misdiagnosed as a cardiopulmonary illness. The main cause of this is the striking resemblance of the symptoms. For instance, clinical signs of paroxysmal supraventricular tachycardia and panic episodes may often be identical, such as palpitations, chest tightness, and dizziness. Differentiating between these entities can be challenging, particularly in cases where there is normal electrocardiographic data.2 Furthermore, the dyspnoea and hyperventilation linked to panic episodes could be mistaken for asthma since both conditions may often display normal spirometry results.3 More frequently the misdiagnosis cases are reported from rural healthcare facilities due to lack of adequate trained medical staff and appropriate diagnostic equipment. The attending physician’s lack of expertise at the first point of interaction may also be contributory factor. In addition, the situation may become complicated by lack of necessary expertise needed assess the psychological components of panic attacks. The misdiagnosis could often results in severe negative consequences leading to unnecessary initiation of therapy thereby severely straining already scarce healthcare resources which could also be detrimental to patient’s health. Without proper psychological care, patients’ panic episodes persist, making them more anxious. Studies indicate that panic disorder is linked to a decline in quality of life, a higher chance of smoking, and an increased risk of suicidal intentions.4 Therefore, it is critical to organise workshops for the physicians in rural Pakistan on recognising the undiagnosed panic disorder. Such educational sessions should be focusing on recognising the unique signs and symptoms of panic disorder, differentiating it from cardiopulmonary conditions. Moreover, it is essential to expand rural residents’ accessibility to psychological care and develop public health initiatives that promote understanding of panic attacks, which can also lessen the stigma attached to mental disorders and assist patients in accessing the right care.